PEMBAGIAN WARIS TERHADAP LAKI-LAKI DAN PEREMPUAN PERSPEKTIF MUHAMMAD QURAISH SHIHAB DAN MUHAMMAD SYAHRUR - Iswatus Sa’adah; Muhammad Muhammad (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This thesis aims to find out how inheritance is distributed according to Muhammad Quraish Shihab and Muhammad Syahrur, aiming to find out how these two figures analyze the distribution of inheritance betwen men and women. This research was carried out using a library research method using descriptive analytical comparative characteristics, namely that the existing data was compiled, described and explained in detail, then analyzed and then compared. The approach used is a normative approach. The result of this research show that in the distribution of inheritance between men and women, the views of Muhammad Quraish Shihab used part 2:1. Meanwhile, Muhammad Syahrur is included in the category of al-hadd al-‘ala and al-hadd al- ‘adna ma’a (1:1).